Odziv sestave telesa, mišične togosti in ravnotežja po 35-dnevni odsotnosti gibanja pri mladih in zdravih preiskovancih - Šimunič, Boštjan (Zdravstveno varstvo, 2008)
Introduction: Sedentary lifestyle causes morphological in physiological changes in both elderly and young people. Horizontal bed rest (BR) is one of the most widely used models for studying the effects of spaceflight, physical inactivity and sedentarism on human body. Our aim was to determine morphological and musculoskeletal changes, and changes in functional balance occurring as a result of total 35-day physical inactivity in persons eating nutritionally well balanced diet adjusted to individual body weight. Methods:Ten healthy young males (age 24.3 2.6 years) were submitted to a 35-day horizontal bed rest in strict hospital environment. Body mass, fat mass, muscle mass, tibial bone mineral content, muscle belly stiffness and postural stability were monitored prior to, during and after bed rest. Results: Body mass dropped by 1 % (P=0.001), muscle mass by 4.1 % (P=0.009) and tibial bone mineral content by 1.7 % (P=0.001), whereas fat mass increasedby 1.4 % (P=0.001). There was a significant decrease in belly muscle stiffness: in the distal head of the vastus medialis muscle it declined from the eighth day of bed rest (P=0.006), and in the proximal head from the very first day of inactivity (P=0.007). After the recovery phase, muscle stiffness returned to baseline levels in the distal head of the vastus medialis only. Postural stability deteriorated by 9.5 % (P=0.000) immediately after bed rest and by 17.4 % (P=0.000) at the first day of recovery. Fourteen days following the period of bed rest no significant postural stability loss was observed. Conclusions: Maintaining nearly neutral energy balance reduces body mass drop and fat mass gain, yet fails to preserve muscle mass or decrease tibial bone loss. The observed decrease in muscle belly stiffness varies among different muscles and occurs during two different phases of cessation and regaining of physical activity. Stance stability tests have proved an effective tool for evaluating postural stability in healthy young men submitted to bed rest.
Keywords: fiziologija; gibalna dejavnost; mišična togost; morfologija; neaktivnost; ravnotežje; tenziomiografija